2011
DOI: 10.1111/j.1600-0633.2011.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the habitat requirement of riverine fish species at the European scale: sensitivity to temperature and precipitation and associated uncertainty

Abstract: Species distribution models (SDMs) have been widely used for different purposes such as studying species niche or forecasting the effects of global change on species distribution. Nevertheless, these models are often calibrated on datasets that only cover a fraction of the species' realised niches, which could lead to unrealistic results. The aim of this study was to model the habitat requirements of 21 freshwater fish species that are native to Europe, using a dataset that accurately reflects their realised n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 79 publications
1
57
1
Order By: Relevance
“…B. barbatula is indeed a cold-to cool-water species whose upper tolerance limit does not exceed 19 xC (Elliott et al, 1996), while the two other cyprinid species prefer warmer waters with an optimum temperature ranging between 12 and 25 xC depending on species and regions (Horoszewicz, 1973;Mann, 1976;Elliott, 1981;Bouchard et al, 1998;Gozlan, 1998;Souchon and Tissot, 2012). When modelling the distribution of stream fish species at the European scale, Logez et al (2012) found a thermal range between 14.1 and 22.6 xC for the stone loach and between 14.7 and 25.8 xC for the chub. These three species were also shown to have contrasted response to future climate change in terms of spatial distribution (Buisson et al, 2008).…”
Section: Fish Speciesmentioning
confidence: 99%
“…B. barbatula is indeed a cold-to cool-water species whose upper tolerance limit does not exceed 19 xC (Elliott et al, 1996), while the two other cyprinid species prefer warmer waters with an optimum temperature ranging between 12 and 25 xC depending on species and regions (Horoszewicz, 1973;Mann, 1976;Elliott, 1981;Bouchard et al, 1998;Gozlan, 1998;Souchon and Tissot, 2012). When modelling the distribution of stream fish species at the European scale, Logez et al (2012) found a thermal range between 14.1 and 22.6 xC for the stone loach and between 14.7 and 25.8 xC for the chub. These three species were also shown to have contrasted response to future climate change in terms of spatial distribution (Buisson et al, 2008).…”
Section: Fish Speciesmentioning
confidence: 99%
“…We used the same data set as Logez et al (2012b). All the data used, except the forecasted climate data, were gathered during the European EFI?…”
Section: Methodsmentioning
confidence: 99%
“…This selection is of major importance because all outcomes will rely on the accuracy of the estimated traitenvironment relationships. The sites chosen had good water quality, no or few modifications of the river cross-section, river channel and water flow, no impoundment, no or few alterations of the river banks and bottom habitat and no major alteration to the river's connectivity (Logez & Pont, 2011;Logez et al, 2012b).…”
Section: Site Selectionmentioning
confidence: 99%
“…Uncertainties intrinsic to future species distribution models based on future climate models are many and varied [38][39][40][41]. Although it has been demonstrated that SDMs contribute significantly to the total variability of future species distribution projections [22,60], the overall uncertainty in suitable future habitats arising from this variability has rarely been considered [56][57][58][59][60].…”
Section: Variability Analysismentioning
confidence: 99%
“…In practice, inherent uncertainty due to the variability of both SDMs and projected future climatic models under different emission scenarios [38][39][40][41] is a particular challenge when considering the reconfiguration of conservation area networks. The variability arising from four different sources, namely: input data, SDMs, General Circulation Models (GCMs) and Greenhouse Gas Emissions Scenarios (GESs) [41,42], is critical in assessing future species distribution uncertainty.…”
Section: Introductionmentioning
confidence: 99%